THE INFLUENCE OF FINANCIAL LITERACY AND SPENDING BEHAVIOR ON YOUNG ADULT EMERGENCY FUND OWNERSHIP IN SURABAYA - Sugiono, Felix; Evelyn, Evelyn (Universitas Muhammadiyah Kalimantan Timur, 2022)
The Covid-19 incident reminds us that having an emergency fund is a crucial allocation outcome for someone in the face of unexpected conditions. The fact is that from various surveys conducted, most Indonesians admit that they do not have adequate emergency funds. This research was conducted to see how financial literacy and spending behavior influence the ownership of emergency funds in young adults in Surabaya. Young adults were chosen in this study because, based on previous studies, in this age range, a person begins to move into a condition of being economically independent and should already be doing financial planning. Data were obtained through questionnaires and processed using logistic regression. The results of the study show that both financial literacy and spending behavior have a significant effect on emergency fund ownership among young adults in Surabaya. This research contributes to the personal finance literature by providing an overview of emergency fund ownership. For young adults, this research can provide insight into the meaning of financial literacy and spending behavior and how these variables can affect one's emergency fund.